The impact on farm household welfare of large irrigation dams and their distribution across hydrological basins: Insights from northern Nigeria - Takeshima, Hiroyuki; Adeoti, Adetola I.; Popoola, Oluwafemi Adebola (International Food Policy Research Institute, 2016)
This study assesses the short-term effects of large irrigation dams on household consumption in the northern part of Nigeria. Using two rounds of the Nigeria LSMS survey, we apply multinomial logit inverse probability weighting (MIPW) methods to construct matching samples across three different types of hydrological basins – dam basins, which are basins that contain large irrigation dams and the area upstream of such dams; downstream basins, which are located downstream of large irrigation dams; and non-dam basins, which are not associated with large irrigation dams. Our analyses particularly focus on the benefits provided by such dams for mitigating the drought risks faced by farm households. Drought is an important factor that affects adversely the welfare of farm household in Nigeria. Supplemental irrigation is often used during drought to provide water to crops.